Supplementation of caffeine to extender improves post-thaw seminal attributes of Poitou donkey semen - KANT, SOURABH; PAL, YASH; LEGHA, R A; RAVI, S K; TALLURI, T R; SHARMA, TARU (The Indian Journal of Animal Sciences, 2021)
The current study was conducted with an objective of elucidating the effect of addition of various levels of caffeine to jack semen on seminal attributes at pre- and post-thaw stage. Six ejaculates from each three adult jack stallions were collected via artificial vagina using estrus jenny as dummy. Caffeine was added to semen extender at 0.1, 0.5 and 2 mM at pre-freeze stage and the semen was cryopreserved according to standard protocol. Sperm motility, viability and other functional attributes were assessed at pre-freeze and post-thaw stages. The present study revealed that, adding caffeine to jack semen extender at 0.1 mM, 0.5 mM or 2 mM levels had positive impact on seminal parameters compared to the control semen. Sperm kinetics (VAP, VSL and STR) and motility increased in the caffeine treated groups in comparison to the control group. The caffeine at 2.0 mM concentration resulted in better post-thaw sperm motility, viability, and acrosome integrity as compared to 1 or 0.5 mM of caffeine and control. Caffeine supplementation also enhanced post-thaw sperm kinematic parameters, which implies its potential as an alternative antioxidant supplement. It was concluded that, 2 mM caffeine supplementation to donkey semen significantly improved post-thaw sperm motility and other functional attributes as compared to the control. However, the potential benefits of caffeine on the fertility rates needs to be investigated.